An efficient access control scheme for smart campus - Niu, Yiru; Jiang, Hong; Tian, Bo; Xiang, Hong; Liu, Yiming; Xia, Xiaofeng; Zhao, Yue (EAI Endorsed Transactions on Scalable Information Systems, 2022)
With the great concern of our country and the continuous development of the epidemic, the development of smart campus is getting faster and faster, the safety of teachers and students becomes more and more important. To ensure the safety of users, the first step is to control at the doors. Usually, the access control method is used in computer system to protect the documents and data, few people use it at doors, but it’s a very effective way to improve safety. So we design a two-factor authentication protocol to verity the user’s identity, and improve the attribute-based access control (ABAC) model to fit the smart campus. We analyze the protocol theoretically and verify its security. Compare with others, our scheme can be more efficient and safer.
Keywords: identity authentication; access control; radio frequency identification (RFID); policy conflict detection